Impalement injuries of the shoulder: a case report with literature review - Scaglia, Marco; Negri, Stefano; Pellizzari, Gianmarco; Amarossi, Andrea; Pasquetto, Davide; Samaila, Elena Manuela; Maluta, Tommaso; Vecchini, Eugenio; Ricci, Matteo; Valentini, Roberto; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2022)
The management of penetrating skeletal extremity trauma is a clinical challenge even for experienced surgeons. While the treatment of associated vascular injuries should be prioritized, there is still a lack of evidence regarding the management of foreign bodies in case of bone fractures or neurological injuries. Here we present a case of impalement of the right proximal humerus with a construction steel rod. The 54-year-old man was successfully treated without vascular, neurological, and thoracic sequelae. A review of the current literature about the most appropriate extrication sequences and soft tissue reconstruction following massive foreign body injuries was carried out.